Desmoplastic histological subtype of ameloblastoma in 16 dogs - Feigin, Kristina; Bell, Cynthia (Frontiers in Veterinary Science, 2024)
Ameloblastoma in dogs most often has a highly conserved acanthomatous cell morphology and is recognized as canine acanthomatous ameloblastoma (CAA) while conventional ameloblastoma (CA) makes up a smaller yet morphologically diverse group of epithelial odontogenic tumors. In humans, a rare desmoplastic histological subtype has distinctive clinical, radiological, and microscopic features. Desmoplastic ameloblastoma (DA) has not previously been described in dogs, although it has been rarely referenced in the veterinary literature. This is the first thorough description of a case series of DA in dogs and describes clinical presentation, diagnostic imaging findings, histopathological features for diagnosis, and treatment outcome. Clinically, DA most often presents as a mass or swelling in the rostral mandible or maxilla of middle age to older dogs. On diagnostic imaging, the lesion has a radiolucent or mixed pattern with well defined borders and variable loculation. As a solid, fibrous tumor with obscured odontogenic epithelium, DA is challenging to diagnose histologically and can mimic several other oral tumors, both benign and malignant. As an ameloblastoma, the biological behavior of DA is locally destructive yet benign and prognosis is favorable following surgical excision.